Pemanfaatan Pos Pembinaan Terpadu (Posbindu) Terhadap Pengendalian Hipertensi Pada Warga Di Tangerang - Riama Marlyn Sihombing; Fiolenty Sitorus; Fransiska Ompusunggu; Triulan Sidabutar; Lisandra Maria G. B. Sidabutar (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2019)
Sustainable Development Goals (SDGs) 2030 had made Non-Communicable Diseases (PTM) as a national priority. PTM - including hypertension - were often undetectable because it had not cause symptoms or complaints and were usually found at an advanced stage so it was difficult to cure and caused disability or premature death. One way to control PTM through Posbindu PTM activities. Purpose of the community service was to find utilization of Posbindu PTM on hypertension control in residents of RW 05 Kelurahan Bencongan Indah Tangerang Banten. Method used quantitative correlation with a cross sectional approached. Population was residents aged 29-85 years with a sample of 83 people. Implementation included measuring blood pressure and monitoring blood cholesterol levels. This community service founded 36.1% of residents who not active used Posbindu PTM, majority (74.7%) were female, more than half (68.6%) showed abnormal blood pressure while results of blood cholesterol test were almost balanced between normal and abnormal results. Data analysis using Fisher's test with an error rate of 0.05 founded a significant difference in blood pressure (p = 0.005) and no difference in cholesterol results (p = 1.00) in the utilization of Posbindu PTM. The future community service activities need to analyze the factors that were related to utilization of Posbindu PTM and improved people's understanding of the importance of Posbindu PTM activities.